Strategi Pengembangan Objek Wisata Hutan Wisata Pinus Lahendong di Kota Tomohon Sebagai Destinasi Ekowisata Unggulan - Tombeg, Marthen R.; Langie, Maureen; Medea, Gloria (Jurnal Sosial Teknologi, 2025)
This study aims to identify and analyze development strategies for the Lahendong Pine Forest tourist attraction located in Tomohon City, North Sulawesi, as a potential leading ecotourism destination. The area possesses significant natural assets, including expansive pine forests, cool climate, and geothermal hot springs, which offer strong attraction for nature-based tourism. This research employed a descriptive qualitative approach, with data collected through direct field observation, in-depth interviews with local stakeholders (including tourism managers, community members, and local government representatives), and documentation review. Data were analyzed to identify key internal and external factors influencing tourism development. The findings reveal that while Lahendong Pine Forest has strong ecological and aesthetic appeal, several challenges hinder its optimal development. These include inadequate supporting infrastructure, limited visitor facilities, weak waste management systems, low promotion intensity, and insufficient community involvement in tourism management. Additionally, the absence of integrated planning has constrained the site’s competitiveness compared to similar ecotourism destinations. Based on the analysis, this study recommends a collaborative and sustainable development strategy involving government authorities, local communities, and private sector actors. Such collaboration should focus on improving eco-friendly facilities, strengthening environmental conservation efforts, enhancing digital promotion, and empowering local communities. The study contributes to ecotourism literature by providing practical insights for sustainable destination development and serves as a reference for policymakers in optimizing nature-based tourism potential in Tomohon City and similar regions.